CORRUPT BEHAVIOR IN A PSYCHOLOGICAL PERSPECTIVE - Winda Putri Diah Restya (Asia Pacific Fraud Journal, 2019)
This study focuses on understanding the corrupt behavior through psychological perspective. The discussion of corruption is always worth to be studied, becauseacts of corruption are different from any ordinary fraud. These actions tend to have a broad impact, and can even make the destruction of a country. This is what distinguishes it from common criminal offenses at the community level. This study seeks to answer the questions on what is the motive underlying corruption, how will the corrupt behavior affect the perpetrators and how are coping strategies undertaken by the corruptor through GONE theory proposed by Jack Bologne: Greed, Opportunity, Need and Exposure. The data of this studies were obtained using qualitative research approach through the in-depth interview method and non-participant observation.. Data were collected in Correctional Institution ClassII B Kajhu – Aceh through three participants. The results show that there are two motives underlying corrupt behavior: Opprtunities and Need, while the motive for Greed is not proven. The impact of corrupt behavior on the individual concerned is the feeling of shame, the loss of self-esteem as a member of the community and also as the head of the family. The coping strategy used by the corruptor was bysuppressing the negative emotions and focusing more on positive thingsuch as being closer to God Almighty.